2000
DOI: 10.1038/sj.mp.4000583
|View full text |Cite
|
Sign up to set email alerts
|

DRD4 exon III VNTR polymorphism—susceptibility factor for heroin dependence? Results of a case-control and a family-based association approach

Abstract: Dopaminergic abnormalities are implicated in the pathogenesis of substance abuse. 1 Recently, two reports have been published suggesting an association between opioid dependence and presence of long alleles of the dopamine D 4 receptor (DRD4) gene exon III VNTR. 2,3 We have attempted to replicate this finding using a two-tiered strategy employing independent case-control and family-based association samples. Our study was possibly the largest candidate gene association study to date on opioid dependence in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 21 publications
1
14
1
1
Order By: Relevance
“…Using the reported z-scores, it is also possible to calculate the effect sizes between the groups (in SD units; d), where d = 0.2 is a small effect size, d = 0.5 is a medium effect size, and d = 0.8 is a Figure 1 Worldwide allele frequencies for the DRD4 exon three VNTR polymorphism. 13,15,[20][21][22]24,[72][73][74][75][76] large effect size. 58 The personality variables were normally distributed.…”
Section: Discussionmentioning
confidence: 99%
“…Using the reported z-scores, it is also possible to calculate the effect sizes between the groups (in SD units; d), where d = 0.2 is a small effect size, d = 0.5 is a medium effect size, and d = 0.8 is a Figure 1 Worldwide allele frequencies for the DRD4 exon three VNTR polymorphism. 13,15,[20][21][22]24,[72][73][74][75][76] large effect size. 58 The personality variables were normally distributed.…”
Section: Discussionmentioning
confidence: 99%
“…Later, however, Li et al (2000) didn't replicate the previous result with a larger sample. Furthermore, a study with German samples failed to find an association between long allele and opioid dependence either (Franke et al 2000).…”
Section: Introductionmentioning
confidence: 96%
“…An excess of the 7-repeat variant of the DRD4 exon III VNTR has been associated with novelty seeking [Ebstein et al, 1996], opiate-dependence [Kotler et al, 1997], alcohol craving [Hutchison et al, 2002], and substance abuse [Vandenbergh et al, 2000]. However, other studies have failed to replicate these associations [Franke et al, 2000;Li et al, 2000].A recent study we carried out showed weak association between the 7-repeat allele of the DRD4 exon III VNTR and methamphetamine abuse in a Chinese population [Chen et al, 2004]. Methamphetamine is a potent psychostimulant with a high dependence on liability and consumption is linked to acute and chronic psychological disturbance, including psychosis.…”
mentioning
confidence: 94%